ANALISIS KOREKSI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL PADA PT POS INDONESIA (PERSERO) - Amelia Ramadhani, Siti Nazwah; Triani, Neks; Nichen, Nichen (Komunitas Manajemen Kompetitif, 2025)
This study aims to evaluate whether the commercial financial statements of PT Pos Indonesia (Persero) comply with applicable tax regulations. A qualitative method with a descriptive approach was used, based on secondary data such as financial reports, books, and articles. The analysis was carried out in three stages: evaluating financial statement accounts, analyzing their conformity with tax regulations, and drawing conclusions. The findings showed that, as of June 30, 2023, tax penalties were recorded as other expenses in the income statement. This is not in line with Article 9 paragraph (1) letter k of the Income Tax Law, which states that tax fines are non-deductible for income tax purposes. Therefore, a positive fiscal correction was made by adding the tax fine amount back to taxable income. This correction results in a more accurate fiscal financial report that complies with tax regulations. Keywords: Commercial financial reports, fiscal financial reports, fiscal corrections